Decision Support System for Giving "joint Degree Program" School of Bhayangkara Surabaya University Using Analyticalal Hierarchy Process (AHP) Method - Irine Ratih Paramitha; Wiwiet Herulambang; Syariful Alim; Arif Arizal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
The granting of scholarships to students is carried out by universities based on their achievements. In awarding scholarships, universities often have difficulty in determining prospective scholarship recipients, so it is found that the distribution of scholarships is not precisely due to a manual system for determining scholarships. Decision support system is an information system intended to assist the University in solving the problem of awarding Academic Achievement Scholarships. One method that can be used in a decision support system is Fuzzy Analitycal Hierarchy Process ( F-AHP) with the Chang model approach (1996). The criteria used are GPA, Achievement, Parents' Work, Parental Dependents and Semesters. From the results of experiments conducted the results of calculations from the application and manual checking from the ubhara get 100% presentation in determining the recipient of the scholarship. Resulting in the ranking of student grades, ten students with the highest grades in each faculty will receive an Academic Achievement Improvement scholarship.